Correlates of health literacy among farmers in northern Thailand - Hannah Montgomery (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Low health literacy is a barrier to public health efforts worldwide. Agricultural workers have an elevated risk for lower health literacy, with important health implications because of their potential exposure to harmful chemicals. The Asian Health Literacy Survey (AHLS) has been developed and translated for use in several different Asian countries and is standardized for easy comparisons across regions. However, it has not been translated for use in Thailand. The purpose of this study was to (1) to determine the health literacy of rural Thai farmers in Northern Thailand, and (2) identify correlates of health literacy within this group. Internal consistency of the Thai AHLS translation was “excellent” (alpha = 0.92). Descriptive results showed that health literacy was relatively high (M = 34.98/50, SD = 6.87). Education, income, working as a village health volunteer, age, length of time farming, no chemical use in farming, health, and pesticide screening were statistically significant correlates of health literacy (R2 = 0.19). Thai farmers had higher health literacy than reported for several other Asian countries. Results may be used to inform the design of future health promotion programs.